CLIL A Helpful Teaching and Learning Approach in the Changing Indian Educational Scenario - Brooks, Tanya Marina (JOURNAL OF INDIAN EDUCATION, 2021)
Approaches towards language teaching and learning always remain under scrutiny in terms of their goals and scope, their aims and their extent. With time, language education has welcomed several approaches from communicative language teaching to cooperative language learning. The approach of Task-based instruction has also seen an increased acceptance as a preferred method for teaching and learning. However, all of the approaches face pertinent questions about how well they work in given circumstances and how they can contribute towards a multilingual language setting. The article aims to introduce the Content and Language Integrated Learning (CLIL) approach as a welcoming alternative to the approaches used at present at various academic levels. and it moves ahead from the traditional approaches. The article presents an intervention study conducted in the city of Guwahati, to highlight the views of students and teacher–observers about the CLIL approach. The study, in a detailed manner, touches upon the stages of pre-intervention, intervention and post-intervention, to give an exact representation of how the approach works and helps the teaching and learning of content and language together. The article reflects findings of the intervention, along with analysis and also highlights the limitations of the study, so as to encourage more research in the area, and to help the approach grow.